Efficient protein depletion by genetically controlled deprotection of a dormant N‐degron - Christof Taxis; Gunter Stier; Roberta Spadaccini; Michael Knop (Molecular Systems Biology)
Abstract Methods that allow for the manipulation of genes or their products have been highly fruitful for biomedical research. Here, we describe a method that allows the control of protein abundance by a genetically encoded regulatory system. We developed a dormant N‐degron that can be attached to the N‐terminus of a protein of interest. Upon expression of a site‐specific protease, the dormant N‐degron becomes deprotected. The N‐degron then targets itself and the attached protein for rapid proteasomal degradation through the N‐end rule pathway. We use an optimized tobacco etch virus (TEV) protease variant combined with selective target binding to achieve complete and rapid deprotection of the N‐degron‐tagged proteins. This method, termed TEV protease induced protein inactivation (TIPI) of TIPI‐degron (TDeg) modified target proteins is fast, reversible, and applicable to a broad range of proteins. TIPI of yeast proteins essential for vegetative growth causes phenotypes that are close to deletion mutants. The features of the TIPI system make it a versatile tool to study protein function in eukaryotes and to create new modules for synthetic or systems biology.